ABUNDANCE OF Acanthaster planci AS HEALTH OF CORAL INDICATOR IN TUNDA ISLAND, SERANG REGENCY, BANTEN - Neviaty P. Zamani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The abundance of Acanthaster planci can be used as a health indicator of coral reef ecosystem. A high abundance of A. planci become phatogen on coral and an indication of unhealthy coral reef ecosystem. The objective of this study was to evaluate health of coral reef ecosystem based on the abundance of A. planci and the percent coral cover at Tunda Island, Banten. Field observation conducted in January 2014. The stations were selected by purposive sampling method and based on four-wind direction i.e., north, south, east, and west. Reef data was measured using Line Intercept Transect (LIT), while sampling method for A. planci using Belt Transect. Results showed that the water temperature ranged of 26-28°C, brightness 100%, current speed ranging between 0.05 ms-1and 0.19 ms-1, and salinity of 30-32 ppt. The water quality values showed a normal range which support the life of the coral and A. planci. The Percent coral cover ranged of 54.95-73.00% indicating a good condition. The abundanceof A. planci was of 0.02-0.03 ind/m2. Result showed that coral cover percentage and the abundance of A. planci did not have a significant relationship. Eventhough an A. planci eats the coral polip, but with small amount of A. planci in the coral reef, they merely help to clean the old and unhealthy polip. This activity will help corals to regenerate their polip. Overall, based on the small abundance of A. planci and the relatively high coral cover percentage, the coral reef ecosystem in Tunda island was categorised in a healthy condition. Keywords: A. planci, coral reef, Tunda Island